India and its visual cultures : community, class and gender in a symbolic landscape - Skoda, Uwe, 1973-; Lettmann, Birgit (New Delhi, India ; Thousand Oaks, California : SAGE Publications, 2018)
"India and its Visual Cultures is a comprehensive mapping and analysis of contemporary cultural artefacts and visual cultures through different approaches--iconographic, social, political, religious, etc. This volume covers various media and their histories. The authors study visual representational systems, production and consumption of media, and culturally specific understandings. Crucial questions about the usage of media in research are also addressed in the book. In the selection of the subjects and objects of enquiry there is a constant engagement with the popular and the everyday. The objects are studied with respect to their situatedness in urban space and everyday life. The five sections of the volume focus on five aspects of visual culture: camera works, folk/artistry, market signs, pictorial politics, and monumental landscapes. With attention to ethnographic detail and anthropology, each section brings an added dimension to the study of visible cultural forms"--Provided by publisher.
Introduction: Mapping visual cultures in India -- Part I. Camera works -- The photograph in social science research : a few ethical and practical questions / Malavika Karlekar -- Unlikely "devis" : gender and imagination on and off the silver screen / Anusuya Kumar -- Visualising death and the corpse : perspectives on post-mortem photographs in central eastern India / Uwe Skoda and Birgit Lettmann -- Part II. Folk/artistry -- 9/11 and the folk artists of Bengal / Roma Chatterji -- From ritual images to animated movies : the transformative journey of the Sora paintings (central eastern India) / Cecile Guillaume-Pey -- Anjan Sen's visual poetry and the Bengal Uttar-Adhunik School / Asunción López-Varela Azcárate -- Part III. Market signs -- The visual culture of meat-shop signs in Delhi / Rita Brara -- The imagery of Indian matchmaking : representations of community, class and gender in a transnational online matrimonial market / Fritzi-Marie Titzmann -- Part IV. Pictorial politics -- A museum, a memorial, and a martyr : politics of memory in the Sikh golden temple / Radhika Chopra -- Divine order, social disorder : debating the visual representations of Laloo Prasad Yadav / Ronie Parciack and Ilanit Loewy Shacham -- Amma provides for all : popular devotional aesthetics, material politics and the Amman in Tamil Nadu / Jill Reese -- Part V. Monumental landscapes -- Building "monuments" in a world-class city : aesthetics and politics of contemporary Delhi / Sushmita Pati -- Mayawati's politics of Sthals : spectacle of the symbolic landscape / Upasona Khound.
Includes bibliographical references and index.
AAL
STS International
Keywords: Visual communication -- India -- History; Art and society -- India -- History; Mass media -- Social aspects -- India -- History; Pictures -- Social aspects -- India -- History; Material culture -- India -- History; Popular culture -- India -- History; English literature; India -- Intellectual life -- 20th century; India -- Intellectual life -- 21st century